Spatiotemporal Sequestration of miR165/166 by Arabidopsis Argonaute10 Promotes Shoot Apical Meristem Maintenance - Yuyi Zhou; Minami Honda; Hongliang Zhu; Zhonghui Zhang; Xinwei Guo; Tianhong Li; Zhaohu Li; Xu Peng; Keiji Nakajima; Liusheng Duan; Xiuren Zhang (Cell Reports, 2015)
Arabidopsis Argonaute10 (AGO10) specifically sequesters miR165 and miR166 and antagonizes their activity, thus regulating shoot apical meristem (SAM) development. However, where and when this sequestration acts is currently unclear. We show here that AGO10 represses miR165/166 activity in the embryo proper during early embryogenesis, through the apical and central regions of mature embryos, and eventually in the entire adaxial domain and vasculature of the cotyledons and leaf primordia. These locations are essentially identical to regions expressing PHABULOSA and REVOLUTA, mRNA targets of miR165/166. The Arabidopsis genome contains nine MIR165/166 genes. Sequestration of miR165/166 by the MIR165b, MIR166a, MIR166b, and MIR166g promoters efficiently rescues the SAM defect in ago10 mutants. Comparison of the expression patterns of AGO10 and the four MIR165/166 members suggests that AGO10 quenches the non-cell-autonomous activity of any miR165/166 that moves into AGO10-expressing niches. Thus, this study provides insight into how the spatiotemporal regulation of AGO10-miR165/166 activity affects SAM development.